2016
DOI: 10.1016/j.bpj.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Binding of NFκB Appears to Twist the Ankyrin Repeat Domain of IκBα

Abstract: Total internal reflection fluorescence-based single-molecule Förster resonance energy transfer (FRET) measurements were previously carried out on the ankyrin repeat domain (ARD) of IκBα, the temporally regulated inhibitor of canonical NFκB signaling. Under native conditions, most of the IκBα molecules showed stable, high FRET signals consistent with distances between the fluorophores estimated from the crystal structures of the NFκB(RelA/p50)-IκBα complex. Similar high FRET efficiencies were found when the IκB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Although we analyzed 109 peptides for IκBα, we realized that a subset of 61 peptides achieve maximal coverage and information content. The results of the newer data, which include complete coverage of AR5, confirmed previous results and were recently published [12]. Similarly, although 69 peptides for RelA and 83 peptides for p50 were analyzed, a subset of 17 peptides from RelA and 18 peptides from p50 that achieve maximal coverage and information content are presented here (Supplementary Figure 1).…”
Section: Resultssupporting
confidence: 85%
“…Although we analyzed 109 peptides for IκBα, we realized that a subset of 61 peptides achieve maximal coverage and information content. The results of the newer data, which include complete coverage of AR5, confirmed previous results and were recently published [12]. Similarly, although 69 peptides for RelA and 83 peptides for p50 were analyzed, a subset of 17 peptides from RelA and 18 peptides from p50 that achieve maximal coverage and information content are presented here (Supplementary Figure 1).…”
Section: Resultssupporting
confidence: 85%
“…Previous NMR experiments showed that resonances in AR3 broaden upon NFκB binding (20), and our results suggest DNA binding further weakens the AR3 structure. Previous single-molecule FRET studies suggested that AR3 senses events at the N-terminal domains of NFκB; in these studies, a subtle twisting of the AR domain accounted for the observed decrease in the FRET signal when the N-terminal domains were included in the binary complex and pointed to a slight structural rearrangement upon formation of the binary NFκB-IκBα complex (29). Here we see that when the ternary complex forms, AR3 senses what is bound to the NFκB N-terminal domains-in this case, DNA.…”
Section: Stripping-impaired Iκbα Is Deficient In Regulating Nfκb In Kmentioning
confidence: 93%
“…Murine N-terminal hexahistidine-RelA 19-321 /p50 39-350 heterodimer (NFκB) was coexpressed as described previously (20) and was purified by nickel affinity chromatography, cation exchange chromatography (Mono S; GE Healthcare), and size-exclusion chromatography (Superdex 200; GE Healthcare). Murine dimerization domain RelA with an N-terminal cysteine and dimerization domain p50 248-350 were expressed, purified, and prepared for surface plasmon resonance (SPR) as described (25,26,29,30). Immediately before the experiments, IκBα was purified by size-exclusion chromatography (Superdex 75; GE Healthcare), and NFκB and NFκB-IκBα complexes were purified by size-exclusion chromatography (Superdex 200) in 25 mM Tris (pH 7.5), 150 mM NaCl, 1 mM DTT, and 0.5 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations